Phonological Substitution In Ibn Hubayrah’s Al-Ifsah ‘An Ma’ani Al-Sihah/ الإبدال الصّوتيّ في الإفصاح عن معاني الصّحاح لابن هبيرة - Omar Hilal khalaf; Jassim Muḥammad Suhayl (Ijaz Arabi Journal of Arabic Learning, 2026)
This research investigates the phenomenon of Phonological Substitution (Al-Ibdal al-Sawti) in the book Al-Ifsah ‘an Ma’ani al-Sihah by Ibn Hubayrah (d. 560 AH). As one of the earliest linguistic commentaries on the Sahihayn, this study explores how Ibn Hubayrah integrated phonological, morphological, and grammatical levels to interpret Prophetic Hadith. Employing a descriptive-analytical approach, the research examines the impact of phonological changes on sound articulation and its subsequent role in semantic interpretation. The findings reveal that Ibn Hubayrah possessed a sophisticated linguistic intuition, enabling him to link phonological variations to Hadith meanings. This study concludes that Al-Ifsah remains a vital source for both Arabic linguistics and Hadith studies.